Fuzzy !-automata and its relationships - Cokilavany, R.; Ven Venkatesan, R.; J. Kavikumar, J. Kavikumar (Academic Publications, Ltd., 2015)
A notion of finite ! - automata with single initial state is proposed. The concept of fuzzy deterministic Buchi automaton and Muller automaton with full acceptance component which is recognize the same fuzzy language are studied. We also establish the relationship between fuzzy deterministic Rabin automaton and Muller automaton. Further, we define the transition fuzzy ! - automata and show that these automata recognize the same fuzzy language as in the fuzzy ! - automata. Finally, we give some closure properties of fuzzy deterministic ! - automata.